2014
DOI: 10.1037/neu0000101
|View full text |Cite
|
Sign up to set email alerts
|

An empirical comparison of the therapeutic benefits of physical exercise and cognitive training on the executive functions of older adults: A meta-analysis of controlled trials.

Abstract: Both treatments improved executive functions, but CT presented a potential advantage at improving executive functions. Improvements in executive functions differed depending on construct for CT, whereas each construct produced similar, modest effect sizes for PE. Publication bias and study quality variability potentially bias these conclusions, as lower quality studies likely produced inflated effect sizes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
73
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 115 publications
(151 reference statements)
3
73
0
2
Order By: Relevance
“…Moreover, greater participation in cognitive, physical and social activity promotes better cognitive performance [52]. A meta-analysis study further suggested the additive benefits of combined physical and cognitive interventions for executive functions in a healthy sample of older adults [10], as well as pronounced cognitive and motor functioning improvements [53]. Lastly, a 6-year longitudinal study revealed that older adults' physical and cognitive engagement was associated with happiness, better functioning, and reduced mortality [54].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, greater participation in cognitive, physical and social activity promotes better cognitive performance [52]. A meta-analysis study further suggested the additive benefits of combined physical and cognitive interventions for executive functions in a healthy sample of older adults [10], as well as pronounced cognitive and motor functioning improvements [53]. Lastly, a 6-year longitudinal study revealed that older adults' physical and cognitive engagement was associated with happiness, better functioning, and reduced mortality [54].…”
Section: Discussionmentioning
confidence: 94%
“…Physical exercise engagement is associated with neurophysiological benefits among older adults, [7] and research suggests that physical activity may buffer against cognitive decline in impaired and healthy older adults [8,9,10], potentially improve cognitive capacities [11], and reduce overall cognitive decline [8]. Psychological and physiological pathologies, such as depression, anxiety, loneliness, psychological stress reactions, and increased circulating levels of cortisol may also be reduced via engagement in physical activity [12,13,14].…”
mentioning
confidence: 99%
“…Regarding future research, more work is needed to better understand when exercise transitions from healthful to harmful. Moderate exercise confers a multitude of health benefits (Brown et al, 2012; Hogan et al, 2013; Karr et al, 2014; Stanton & Reaburn, 2014), yet excessive exercise has extremely deleterious effects (Mond et al, 2004; O’Keefe et al, 2012; Williams & Thompson, 2014). Thus, it is possible that the relationship between exercise and health is curvilinear—this would mean that after reaching a certain threshold, exercise becomes exponentially more harmful.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of regular, moderate physical activity range from decreasing the risk of cancer (Brown, Winters-Stone, Lee, & Schmitz, 2012) to improving cognition (Hogan, Mata, & Carstensen, 2013; Karr, Areshenkoff, Rast, & Garcia-Barrera, 2014) and improving outcomes for treatment-resistant major depression (Stanton & Reaburn, 2014). However, not all amounts and types of physical activity confer health benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Como fator preventivo e de controle destas alterações, o exercício físico vem a contribuir para a conservação ou até mesmo melhora das alterações abordadas acima, pois ao se desenvolver um determinado tipo de exercício físico, devemos levar em consideração a necessidade do mesmo, assim procurando sempre a facilitar a execução das AVDs de idosos (PLUMMER et al, 2016;CHAN et al, 2015;ZHANG;SHUAI, 2015;KARR et al, 2014;GINÉ-GARRICA et al, 2014;VRIES et al, 2012).…”
unclassified